Dea Roma and the Roman virtues : a comparative study in the policy and practice of Deified abstractions - Sharp, James Edward (School of Languages and Literatures, 2015)
The purpose of this thesis is to provide an in-depth study of the goddess Roma and the development and spread of her cult across the eastern and western halves of the Roman Empire from the second century BC to the reign of Augustus. In the east the institution of her cult was the result of expanding Roman influence in the region, and served as a means for people to conceptualise the presence of Roman power. In contrast to this, her worship in the west, as part of the imperial cult, was mandated by the emperor Augustus. In order to better understand the place of Roma in the context of the western empire, I argue that it is best to view her as a deified abstraction. The deified abstractions were a group of divinities in Rome that embodied a specific ideal or concept (the goddess Concordia embodying concord, Pax embodying peace etc.). In order to view the goddess in this manner, I examine what it meant for Roma to embody "Rome", and what this would have meant to the people who worshipped her. This examination also takes into account the views of scholars such as Mellor, who view Roma as little more than a political tool and a by-product of Greek sycophancy, as well as those scholars who view the deified abstractions in Rome as a carry-over of archaic Roman religion that held little importance to the people of Rome. Such opinions, I argue, are both erroneous and untenable.